Chemotherapy and radiation induced pulmonary dysfunction in hodgkin lymphoma patients - İzmir Güner, Şebnem; Teoman Yanmaz, Mustafa; Selvi, Ahmet; Usul, Çiğdem (My University, 2016)
Although the deterioration in pulmonary functions is a well-known important problem due to the treatment of the Hodgkin's lymphoma patients, the immediate and long term effects of the therapy and its distinctive components were not shown clearly yet. We planned to investigate effects of multiple agent chemotherapy and/or radiotherapy to pulmonary functions immediately and thereafter and the possible effects of the managing this situation. 34 patients were included the study. The patients were evaluated for peak expiratory flow (PEF), forced expiratory volume in 1 s (FEV1), forced expiratory vital capacity (FVC), mean total lung capacity (TLC) values, FEV1/FVC ratio, diffusing capacity for carbonmonoxide (DLco), diffusing capacity for carbonmonoxide corrected for hemoglobin concentration (DLCO) before and at 1, 6 and 12 months after the initiation of the treatment. Demographic characteristics; disease stages; chemotherapy protocols; whether radiotherapy is received; if yes, the region and the dose received were recorded. The tests were finally analysed in two separated groups; group A treated with only chemotherapy and group B; treated with combination therapy, chemotherapy and radiotherapy. In group A, FVC and FEV1 is similar before and after treatment. FEV1/FVC ratio was increased (P = 0.0001) in this group despite increasing in mean TLC values (P = 0.001). No meaningful changes were observed in PEF and DLCO values in group A. In group B, FVC, FEV1 and PEF were decreased after treatment (for FVC P = 0.028, for FEV1 P = 0.04). Despite a decrease in first month of the treatment in FEV1/FVC ratio and DLco these two parameters were recovered at the end of the first year in group B patients. TLC values were increased after treatment in group B as in group A (P = 0.035). We believe that, if these patients are managed well in 1 year; necessary precautions are provided; and patients are well-informed, then there wouldn't be too much risk and mortality rate for long-term side effects of ABVD and mediastinal RT.
Keywords: Chemotherapy; Hodgkin lymphoma; Pulmonary Dysfunction; Radiation